ELEKTRODEKOLORISASI ZAT WARNA REMAZOL VIOLET 5R MENGGUNAKAN ELEKTRODA GRAFIT - Karmanto Karmanto; Riana Sulistya (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2014)
Research of decolorization technique development with electrolysis method used graphite electrodes and Na2SO4 as the electrolyte solution has been done. This study was conducted to assess the capabilities of graphite electrodes in electrodecolorizer cell and the adding effect of Na2SO4 in remazol violet 5R dyes decolorization. the assessment on electrodecolorizer cell performance had been done by electrolyzing 50 ml solution of remazol violet 5R, at 5 V of voltage in the Na2SO4 electrolyte solution. The electrolysis had been done based on the variation of the contact time, up to 120 minutes. On the other hand, study on the adding effect of the Na2SO4 salt solution had been done by the absorbance measuring of the remazol violet 5R dye remained in the solution, as the result of electrolysis process in the various concentrations of Na2SO4: 0.025 ; 0.05, 0.1, 0.5 and 1 M. The result shows that electrolysis using graphite electrode on the elektrodecolorization process of the remazol violet 5R dye, has dye digression capability up to 83% for 90 minutes without precipitate forming. The elektrodecolorization kinetics reaction of the violet Remazol-5R dye, appropriate to the first order reaction kinetics equation with a coefficient of reaction rate 0.017 ppm/minute. While the variation of the salt concentration in electrolysis process, showing that the percentage of the remazol violet 5R dye degraded increased along with the amount of Na2SO4 concentrations used. Based on UV-Vis spectrophotometry analysis, there is no absorption spectra observed at a wavelength of 200-700 nm in the violet Remazol-5R dye solution after electrolysis process. It means that the chromophore group of the remazol violet 5R, had been degraded.